Challenges Newly Appointed Female Principals Encounter Executing Instructional Leadership: Context of Rural Primary Schools - Saltiel Khololo Collen Mataboge (Iranian Journal of Educational Research)
Objective: This conceptual paper seeks to explore the challenges newly appointed female principals encounter in executing instructional leadership within the context of rural primary schools. The main question for the study is: What are the key obstacles that newly appointed female principals face in implementing effective instructional leadership in rural educational settings? Methods: This paper adopts a qualitative approach, with data collection rooted in an extensive review of scholarly studies, recent books and peer-reviewed articles. The data is analyzed within the interpretive paradigm which generates a deeper understanding of the intricate challenges faced by these female leaders. Results: Findings suggest that newly appointed female principals in rural schools often grapple with issues such as gender bias, limited access to professional development, community resistance to female leadership and inadequate resources. Practical implications include the need for targeted leadership training programs, mentorship opportunities and community engagement strategies to support newly appointed female principals in these challenging environments. Conclusions: By mitigating these challenges, the study provides valuable insights for policymakers, teachers and stakeholders with the aim to enhance the effectiveness of instructional leadership in rural primary schools thereby quality education.